THE PROBLEM OF MOTIVATION AND METHODS OF ITS INCREASE AT STUDENTS OF NOT LANGUAGE TRAINING DIRECTION IN TEACHING FOREIGN LANGUAGE - Olga A. Danilova (Integraciâ Obrazovaniâ, 2016)
Introduction: the article is devoted to such an actual today issue as increasing of motivation of students learning foreign languages in non-language faculties of a contemporary university. The authors identify the main reasons causing the low level of language preparation among students of non-linguistic directions of preparation, which include – lack of motivation for the implementation of utterance (dominated by a strong belief that in real life it is not useful); small vocabulary; poor knowledge (or ignorance) of grammar of the language being studied; the fear of making a mistake (“psycholo gical barrier”).